Use of vacuum-assisted closure in massive puerperal genital hematoma - Emsal Pinar Topdagi Yilmaz; Omer Erkan Yapca; Gamze Nur Cimilli Senocak; Yunus Emre Topdağı; Ragip Atakan Al (Korean Society of Obstetrics and Gynecology, 2019)
Puerperal genital hematomas are rare but life-threatening complications of obstetric emergencies. A pregnant patient (39 weeks) underwent a mediolateral episiotomy during a vaginal delivery. An afterbirth hematoma (approximately 20 cm in diameter) was evacuated, but the use of a vacuum-assisted wound closure system was applied after the sutures opened on the 7th postoperative day. On the 10th day of the vacuum-assisted closure (VAC) application, the wound was completely closed. VAC is an alternative treatment modality that can drain an infection and increase the proportion of granulation tissue in humid and irregular surfaces such as the perineum.